The FABS trial: a randomised control trial of the effects of a 6-month physical activity intervention on adherence and long-term physical activity and self-efficacy in older adults with memory complaints - Cox, K.; Flicker, L.; Almeida, O.; Xiao, J.; Hendriks, Jacqui; Phillips, M.; Lautenschlager, N. (2013)
Objective: The aim of this study is to assess in older adults with memory complaints, the effects of a 6-month home-based physical activity (PA) intervention on short-term adherence, short and long-term self-efficacy and the predictors of adherence. Methods: Participants with memory complaints with or without mild cognitive impairment (MCI) were recruited from Perth, Western Australia between May 2004 and July 2006 and randomly assigned to a control or an intervention group. The intervention group received a 6-month PA programme and recorded sessions on a diary. Pedometer readings, questionnaires, and physical and cognitive measures were completed at 0, 6, 12 and 18 months. Results: One hundred and seventy participants started the study. Retention rates were similar for both groups at all time-points however retention was higher for men than women (P < 0.01). Adherence to the prescribed PA was 72.8% (95% CI, 70.8 74.9%). Men had higher adherence rate than women (P < 0.001). Those with and without MCI had similar adherence. Compared to controls self-efficacy was higher in the intervention group after 6 months only (P < 0.01). Conclusions: Older adults with memory complaints, with or without MCI, can successfully participate in and enjoy home-based PA programmes. Long-term adherence to such interventions may require continued support and increased self-efficacy. (Trial registration: ACTRN012605000136606.)